THE INFLUENCE OF CUSTOMER SATISFACTION, TRUST, AND SERVICE QUALITY ON THE LOYALTY OF CUSTOMERS WHO PURCHASE HEALTH INSURANCE AT PT ASURANSI ALLIANZ UTAMA INDONESIA - Situmeang, Rosinta Romauli; Georgiana Ruby; Bintang Lie; Joan Million Sintara; H. Aldwin Surya (Institut Teknologi dan Bisnis Kristen Bukit Pengharapan, 2024)
The purpose of this research is to find out how client loyalty is to PT. Allianz Utama Indonesia Insurance is influenced by factors such as customer satisfaction, trust and service quality. This research is descriptive in nature. The 1,116 participants in this research were PT. Indonesia's Main Allianz Insurance Client. Using the Slovin formula, the research sample consisted of 92 people, and the sampling process used basic random sampling. Analysis using multiple linear regression is the statistical technique used. Research findings show that factors such as customer satisfaction, trust, and expressed service quality partially influence customer loyalty. Moreover, it reveals the relationship between client loyalty, service quality, and customer happiness all at once. Research findings show that client loyalty to PT. Allianz Utama Insurance Indonesia when purchasing health insurance is influenced simultaneously and to a certain extent by factors such as customer satisfaction, trust and service quality.